Colonization history of Galapagos giant tortoises: Insights from mitogenomes support the progression rule. (21st September 2020) - Poulakakis, Nikos; Miller, Joshua M.; Jensen, Evelyn L.; Beheregaray, Luciano B.; Russello, Michael A.; Glaberman, Scott; Boore, Jeffrey; Caccone, Adalgisa
Abstract: Galapagos giant tortoises ( Chelonoidis spp.) are a group of large, long‐lived reptiles that includes 14 species, 11 of which are extant and threatened by human activities and introductions of non‐native species. Here, we evaluated the phylogenetic relationships of all extant and two extinct species ( Chelonoidis abingdonii from the island of Pinta and Chelonoidis niger from the island of Floreana) using Bayesian and maximum likelihood analysis of complete or nearly complete mitochondrial genomes. We also provide an updated phylogeographic scenario of their colonization of the Galapagos Islands using chrono‐phylogenetic and biogeographic approaches. The resulting phylogenetic trees show three major groups of species: one from the southern, central, and western Galapagos Islands; the second from the northwestern islands; and the third group from the northern, central, and eastern Galapagos Islands. The time‐calibrated phylogenetic and ancestral area reconstructions generally align with the geologic ages of the islands. The divergence of the Galapagos giant tortoises from their South American ancestor likely occurred in the upper Miocene. Their diversification on the Galapagos adheres to the island progression rule, starting in the Pleistocene with the dispersal of the ancestral form from the two oldest islands (San Cristóbal and Española) to Santa Cruz, Santiago, and Pinta, followed by multiple colonizations from different sources within the archipelago. Our work provides an example of how to reconstruct the history of endangered taxa in spite of extinctions and human‐mediated dispersal events and provides a framework for evaluating the contribution of colonization and in situ speciation to the diversity of other Galapagos lineages. Abstract : We analyzed the mitochondrial genomes of Galapagos giant tortoises ( Chelonoidis spp.) to evaluate the phylogenetic relationships of all extant and two extinct species and provide a new phylogeographic scenario of their colonization of the Galapagos Islands. The resulting analyses suggest that their diversification on the Galapagos adheres to the island progression rule, starting in the Pleistocene with the dispersal from the oldest islands (San Cristóbal and Española) to the most recent ones.